2011 19th International Conference on Geoinformatics 2011
DOI: 10.1109/geoinformatics.2011.5981165
|View full text |Cite
|
Sign up to set email alerts
|

The change detection of impervious surface and its impact on runoff in the Qinhuai River Basin, China

Abstract: The changes of impervious surface from 1986 to 2006 and the relationship between those changes and hydrological response were studied in the Qinhuai River Basin (2631 km 2 ), which is located in the southwest of Jiangsu Province, P. R. China. A series of Landsat imagery during that period was employed to extract impervious area using the Linear Spectral Mixture Analysis. The results showed that impervious area increased from 2.9% in 1986 to 12.1% in 2006. The annual runoff and precipitation of the basin were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…For example, a simulation study in Taiwan suggested that rice paddy fields generated 55 % lower total runoff and 33 % lower peak flows than dry farms (Wu et al, 1997). However, another simulation study that used the HEC-HMS model for a rice paddy-dominated watershed in southern China found that an increase in impervious surface areas from 3 to 30 % increased the peak-flow rate and storm volume (4-20 %), but had a very limited impact on total annual flow (< 6 %) Du et al, 2011Du et al, , 2012 and thus long-term water balances.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a simulation study in Taiwan suggested that rice paddy fields generated 55 % lower total runoff and 33 % lower peak flows than dry farms (Wu et al, 1997). However, another simulation study that used the HEC-HMS model for a rice paddy-dominated watershed in southern China found that an increase in impervious surface areas from 3 to 30 % increased the peak-flow rate and storm volume (4-20 %), but had a very limited impact on total annual flow (< 6 %) Du et al, 2011Du et al, , 2012 and thus long-term water balances.…”
Section: Introductionmentioning
confidence: 99%
“…During 2000-2012, the QRB went through dramatic landcover changes characterized by an increase in urban areas and a decrease in paddy fields (Du et al, 2011(Du et al, , 2012Chen and Du, 2014) (Fig. 2).…”
Section: Land Conversion and Change In Laimentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, 16.5% of rice-wheat rotation fields with high ET were converted into urban area characterized by low vegetation coverage with low ET from 2000 to 2013. Thus, the watershed hydrological cycle has been altered [2,6,34,69]. An early study by Hao et al [2] confirmed that the remarkable impacts land use and land cover change have overwhelmed the effects of climate in the QRB.…”
Section: Effects Of Land Use and Land Cover Changes On All Et Componentsmentioning
confidence: 99%